Problemática associada à utilização de diferentes tipos de mochila para transporte de material escolar - Oliveira, Elsa (2014)
Load transportation is a common task in young students. They need to move to the schools personal objects, books and other stationery. However, this task can be the cause of musculoskeletal disorders in the students. In view of this, this work aims to characterize the problem of the backpack used by the students and to determine the Maximum Acceptable Weight (MAW) and the Rating of Perceived Exertion (RPE) for the task of backpack transportation, through a psychophysical approach. Students of the 7º, 8º and 9º classes were included. The study was divided in two different phases. In the first phase it was applied two questionnaires to analyse the problem of the different backpack used by the students. It was analysed issues related with the type of backpack used, its characteristics and students’ routines. The weight of the backpack, as well as the height and weight of 131 students were also determined. The results showed that backpack with two shoulder straps were the most used. However, several students only use one strap. The majority of the students reported to feel pain during the backpack transportation. In the second phase, it was determined the MAW and the RPE with a sample of 10 students. The task was to carrying the backpack with both shoulders, with the straps correctly adjusted to the body, during a pre-defined rout, according to the experimental procedure. The MAW determined by the students was 6.8 kg. The region of the shoulders was identified as presenting more pain during the task. This study emphasizes the need of a better awareness of the students and parents about this problem.